Pendampingan Pengolahan Keripik Jamur di UKM Jamur Tiram, Desa Bengle, Kabupaten Boyolali - Fatmasari Sukesti; Dyah Nirmala Arum Janie; Nurcahyono Nurcahyono; Nur Khatik; Erma Handarsari; Ida Kristiana; Bana Ahmad Gautama (LPPM UNIVERSITAS DIAN NUSWANTORO, 2023)
UKM Kelompok Tani jamur tiram